2017
DOI: 10.3892/ol.2017.6250
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of patients with intrahepatic cholangiocarcinoma based on serum periostin may be predictive of prognosis

Abstract: An effective serum biomarker may improve cholangiocarcinoma (CCA) management. Periostin (PN) has been demonstrated to be associated with aggressive CCA. The current study evaluated PN in blood serum for its diagnostic and prognostic potential in patients with CCA. Sera of 68 patients with CCA were collected prior to treatment, and PN levels were measured using an ELISA. Sera from 50 normal controls, 6 patients with benign liver diseases, 2 with hepatocellular carcinoma and 21 with breast cancer were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 62 publications
1
24
2
Order By: Relevance
“…Our results demonstrating a strong positive correlation between increasing levels of both tumor and serum Postn as a function of increasing liver cholangiocarcinoma tumor size, enhanced desmoplastic stroma, and increased gross peritoneal metastases in BDEneu tumor‐bearing rats also strongly support stromal Postn overexpression as being predictive of progressive cholangiocarcinoma growth in our rat cholangiocarcinoma model. Our findings are thus compatible with the findings of Utispan et al6 and Thuwajit et al11 for human ICC. In contrast, rats with biliary cirrhosis induced by bile duct ligation were previously demonstrated by us not to exhibit measurable levels of Postn protein expression by either immunohistochemistry or western blot analysis 1…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results demonstrating a strong positive correlation between increasing levels of both tumor and serum Postn as a function of increasing liver cholangiocarcinoma tumor size, enhanced desmoplastic stroma, and increased gross peritoneal metastases in BDEneu tumor‐bearing rats also strongly support stromal Postn overexpression as being predictive of progressive cholangiocarcinoma growth in our rat cholangiocarcinoma model. Our findings are thus compatible with the findings of Utispan et al6 and Thuwajit et al11 for human ICC. In contrast, rats with biliary cirrhosis induced by bile duct ligation were previously demonstrated by us not to exhibit measurable levels of Postn protein expression by either immunohistochemistry or western blot analysis 1…”
Section: Discussionsupporting
confidence: 94%
“…Patients with cholangiocarcinoma were also reported to exhibit a significantly higher median Postn level in their serum than those with normal liver, liver cirrhosis, HCC, or other malignancies 10. High serum and tumor tissue samples with high Postn expression detected by immunohistochemistry have been significantly associated with reduced survival in patients with ICC,11 which suggests that elevated serum Postn may be used to divide such patients into low and high Postn groups.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, similar results were observed. Thus, serum POSTN levels in patients with cholangiocarcinoma were significantly increased compared with that in healthy controls, patients with benign liver diseases, and even patients with breast cancer, indicating that serum POSTN levels could be used as a diagnostic biomarker ( 96 ). Furthermore, high levels of serum POSTN, as well as tissue POSTN levels, were significantly associated with reduced survival rate.…”
Section: Serum Postn Levels As a Biomarker Of Poor Prognosismentioning
confidence: 99%
“…Furthermore, high levels of serum POSTN, as well as tissue POSTN levels, were significantly associated with reduced survival rate. Serum POSTN was identified as an independent prognostic factor suggesting that it could be used as a marker of poor prognosis in patients with cholangiocarcinoma ( 96 ).…”
Section: Serum Postn Levels As a Biomarker Of Poor Prognosismentioning
confidence: 99%
“…Thus, these two independent interaction-induced signaling pathways are important for the development and maintenance of cancer cells [ 40 ]. Elevated levels of POSTN have been detected in sera from patients with various types of cancers [ 45 , 46 , 47 ], suggesting that POSTN may be a useful biomarker for those cancers. The detection of POSTN by the immunohistochemical (IHC) staining of tumor lesions by anti-POSTN mAbs targeting the fasciclin domain, which can inhibit integrin-mediated cell migration in vitro, has also been reported [ 48 ].…”
Section: Current Knowledge Regarding the Roles Of The Matricellulamentioning
confidence: 99%